EFIKASI EKSTRAK Ageratum conyzoides SEBAGAI PENGENDALI GULMA PASCA TUMBUH PADA BERBAGAI KONSENTRASI - Retno Muningsih; Ikbar Thomi Firdausi; Sukarji; Gunawan Ciptadi (Jurnal Ilmiah Media Agrosains, 2022)
Weeds are plants whose presence is not desired in the planting area because they are considered detrimental, inhibiting plant growth and production. The losses caused by the presence of weeds in cultivated areas can be very large, but these losses are rarely measured because weeds and cultivated plants are both plants (plants). Chemist weed control is widely used because the effects are seen more quickly and in an easier way. There can also be competition between weeds because of the allelopathy that can suppress the growth of fellow weeds and/or cultivated plants. Allelopathy is one of the ingredients that can be used as a herbicide biological material. Ageratum conyzoides contains chemical compounds from the class of alkaloids, anthraquinones, terpenes, steroids, tannins and phenols that can inhibit cell division germination, and inhibit the growth and/or development of weeds/other plants. This study aimed to determine the efficacy of Ageratum conyzoides extract used as a biological herbicide and obtain a concentration of Ageratum conyzoides extract which could be used as a biological herbicide. The experiment was carried out at the Krajan Practice Gardens, Polytechnic LPP Yogyakarta, with treatment concentrations of extracts of Ageratum conyzoides, namely 0% (A0), 1% (A1), 3% (A2), 5% (A3) and 7% (A4) per m² sample plot. Treatment A3 (3% concentration) was the concentration that caused the greatest poisoning symptoms compared to treatments A5 (5% concentration), A7 (7%), A1 (1% concentration) and A0 (0% concentration).